Conditioned Medium from Human Amnion-Derived Mesenchymal Stem Cells Regulates Activation of Primary Hepatic Stellate Cells - Qingjie Fu; Shunsuke Ohnishi; Naoya Sakamoto (Stem Cells International)
Mesenchymal stem cells (MSCs), or multipotent mesenchymal stromal cells, are present in almost all organs and tissues, including the amnion. Human amnion-derived mesenchymal stem cell (hAMSC) transplantation has been reported to ameliorate liver fibrosis in animal models. However, the mechanism for the prevention of liver fibrosis is poorly understood. In this study, we investigated the effects, and underlying mechanisms, of a conditioned medium obtained from hAMSC cultures (hAMSC-CM) on a primary culture of rat hepatic stellate cells (HSCs). We observed that in routine culture, hAMSC-CM in HSCs significantly inhibited the expression of alpha-smooth muscle actin (α-SMA), an activation marker of HSCs, and the production of collagen type 1 (COL1), a dominant component of the extracellular matrix (ECM) in the culture medium. In addition, hAMSC-CM upregulated the expression of ECM degradation-related genes, such as metalloproteinase- (Mmp-) 2, Mmp-9, Mmp-13, and tissue inhibitor of metalloproteinase- (Timp-) 1; however, it did not affect the expression of collagen type 1α1 (Col1a1). These regulatory effects on HSCs were concentration-dependent. A cell proliferation assay indicated that hAMSC-CM significantly suppressed HSC proliferation and downregulated the expression of cyclin B (Ccnb), a proliferation-related gene. Transforming growth factor-beta (TGF-β) treatment further activated HSCs and hAMSC-CM significantly inhibited the upregulation of α-Sma and Col1a1 induced by TGF-β. These findings demonstrated that hAMSC-CM can modulate HSC function via secretory factors and provide a plausible explanation for the protective role of hAMSCs in liver fibrosis.